Woodcarving - 501971 Ellenwood, Everett (East Petersburg, P.A. : Fox Chapel Publishing)
All you need are sharp tools, a piece of wood, and an imagination to create your own works of art by carving wood. Seven woodcarving projects include all the information you need for success, including tool lists, materials and supply lists, skill lists, and step-by-step photographic instructions especially designed for kids. --